2013
DOI: 10.1042/bst20120273
|View full text |Cite
|
Sign up to set email alerts
|

The role of microvesicles in cancer progression and drug resistance

Abstract: Microvesicles are shed constitutively, or upon activation, from both normal and malignant cells. The process is dependent on an increase in cytosolic Ca2+, which activates different enzymes, resulting in depolymerization of the actin cytoskeleton and release of the vesicles. Drug resistance can be defined as the ability of cancer cells to survive exposure to a wide range of anti-cancer drugs, and anti-tumour chemotherapeutic treatments are often impaired by innate or acquired MDR (multidrug resistance). Microv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 53 publications
3
33
0
Order By: Relevance
“…A large number of these target genes were involved in the MAPK, RAS, p53, ErbB, Janus kinase-STAT, TGFβ, mTOR and Wnt signaling pathways, which are known to be associated with leukemia (4450). Consistent with other cancers (51–53), the role of leukemia-derived MVs was to modulate the disease progression rather than being the main cause of the disease itself. MVs from leukemia cells facilitate leukemia progression and invasion in different ways (15,5456).…”
Section: Discussionsupporting
confidence: 66%
“…A large number of these target genes were involved in the MAPK, RAS, p53, ErbB, Janus kinase-STAT, TGFβ, mTOR and Wnt signaling pathways, which are known to be associated with leukemia (4450). Consistent with other cancers (51–53), the role of leukemia-derived MVs was to modulate the disease progression rather than being the main cause of the disease itself. MVs from leukemia cells facilitate leukemia progression and invasion in different ways (15,5456).…”
Section: Discussionsupporting
confidence: 66%
“…Microvesicles that originate from the outward budding and fission of the plasma membrane are distinct from exosomes produced by multivesicular bodies, which are released upon fusion with the plasma membrane [116]. In fact, microvesicles are important regulators of transferring proteins and RNAs that influence tumor progression and drug resistance [117]. Secreted molecules such as exosome vesicles and microvesicles are occasionally modifiers of tumor characteristics that influence the microenvironment.…”
Section: Tumor Heterogeneity With Similar Characteristics To Tumor MImentioning
confidence: 99%
“…This radical reduction in EV shedding prevents the cancer cells from carrying out active drug efflux through EV shedding, and thus sensitizes them to chemotherapeutic drugs ( Figure 2). Accordingly, other studies performed in our laboratories show that neoplastic cells are rendered more sensitive to cancer drugs when EV biogenesis is inhibited [11,71]. We have also shown that EV inhibition via a calpeptin inhibitor or siRNA limits tumour growth in vivo, emphasizing the important role of EV generation and manipulation for tumour growth [53].…”
Section: Pad Inhibitors In Synergy With Chemotherapeutic Drugsmentioning
confidence: 99%
“…Interestingly, EV shedding from cancer cells also aids increased active drug efflux and thus contributes to their resistance to chemotherapeutic agents [11,52]. In addition, inhibition of microvesiculation has been shown to render cancer cells more susceptible to anticancer drug treatment [7,11] and to reduce the dose of anti-cancer drug docetaxel required to limit tumor growth in vivo [53].…”
Section: Evs In Cancermentioning
confidence: 99%
See 1 more Smart Citation